Effectiveness of Nutrition Education as Intervention on Complementary Feeding Practices & Growth of Children in Rural Area - Mallesh, Vidya; Patil , Shailaja S (National Journal of Community Medicine, 2024)
Background: The first 2years of a child's, feeding-pattern is an important determinant of childhood-malnutrition. Nutritional education on complementary feeding was provided, and the impact on Minimum-Meal-Diversity [MMD], Minimum-Meal-Frequency [MMF] & the children's growth, was evaluated & compared between the education-intervention group and the control group. Methodology: The study was conducted in 2villages of Vijayapura-district 5Anganwadi from each village was selected for study and compared. Primary-outcome: improvement in MMD, MMF Secondary-outcome: weight for age Z-score [WAZ], weight for age Z-score [HAZ] &mid-arm-circumference. Results: Overall education-intervention-group showed better weight-gain than control-arm significant-difference was observed in WAZi.e1.36 v/s1 (p<0.0017*) & HAZ-3.82 v/s -4 (p<0.00078*) respectively. In Intervention-arm mothers following MMF significantly increased &was statistically significant. There was a significant rise in the percentage of mothers in the intervention group who adopted MMD for their children. (p<0.0001*). Gender differences in mean WAZ scores &HAZ were observed in both groups persistently throughout the study period & were statistically significant. Conclusion: Program interventions need to understand the local practices &needs of mothers & tailor interventions and nutritional education to improve child feeding practices including hygienic practices with regular follow-ups, is vital to prevent the vicious cycle of malnutrition.